IMPLEMENTASI AKAD MURABAHAH TERHADAP PEMBIAYAAN PENSIUN PADA BANK SYARIAH BUKOPIN KC SURABAYA - Meyrina Ferdiana Putri; Sunan Fanani (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The purpose of this study was to determine how the application of Murabahah contract on pension financing product in Bank Syariah Bukopin KC Surabaya. Things that need to be reviewed in the practice of contract murabahah is tailored to the specific points on the National Sharia Board Fatwa Indonesian Ulama Council Fatwa No.04/DSN-MUI/IV/2000 about murabahah. This study uses a qualitative method with descriptive case study strategy. The object of this study is Bank Syariah Bukopin KC Surabaya. By conducting interviews to 3 respondents consisting of Account Officer, Financing Operations, and Marketing staff. After the interviews were analyzed using the pairing patterns to get conclusion. The result of research conducted by observation and interview by 3 respondents, tthe product of pension financing that Bank Syariah Bukopin KC Surabaya in accordance with Fatwa DSN-MUI No.04 / DSN-MUI / IV / 2000 about murabaha.Keywords: Implementation of Murabahah contract, DSN-MUI, Pension Financing, Bank Syariah Bukopin KC SurabayaREFFERENCESDsnmui.or.id diakses pada 5 mei 2018 pukul 14.41www.ojk.go.iddiakses pada 29 april 2018 pukul 20.15Karim A, Adiwarman. 2014. Bank Islam: analisis fiqih dan keuangan. Jakarta. PT. Raja Grafindo Persada.Sugiyono, Prof. Dr. 2012. Metode Penelitian Kuantitatif, kualitatif, dan R&D. Bandung: Alfabeta. Ascarya,2013. Akad dan Produk Bank Syariah. Jakarta:PT. RajaGrafindo PersadaWiroso, 2005. Jual Beli Murabahah. Yogyakarta: UII PressWidodo, 2014. Teori dan Implementasi. Edisi revisi. Yogyakarta: Penerbit AndiYin, Robert K. 2009. Studi kasus: desain& Metode. Jakarta:  Prenada media.Antonio, Muhammad Syafi’i, 2001. Bank Syari’ah: dari Teori ke Praktik. Jakarta: Gema Insani Press